2020
DOI: 10.1002/ppul.25138
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopy versus thoracotomy for congenital lung malformations treatment: A single center experience

Abstract: Introduction Our aim is to compare thoracoscopy to thoracotomy in the treatment of congenital lung malformations (CLM) in children. Materials and Methods We report a retrospective monocentric cohort study. Patients treated at our Center for CLM (1991–2020) were divided in two groups: patients treated with video‐assisted thoracoscopic surgery (VATS) and open thoracotomy (OT). Characteristics of the two groups were compared through statistical analysis (GraphPad Prism7). A p value less than .05 was considered st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Conversion rates in thoracoscopic lobectomy has been reported between 0-33% [10][11][12]. In our study, the conversion rate was 10% which seems to be in accordance with current literature [10,13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conversion rates in thoracoscopic lobectomy has been reported between 0-33% [10][11][12]. In our study, the conversion rate was 10% which seems to be in accordance with current literature [10,13].…”
Section: Discussionsupporting
confidence: 92%
“…Conversion rates in thoracoscopic lobectomy has been reported between 0-33% [10][11][12]. In our study, the conversion rate was 10% which seems to be in accordance with current literature [10,13]. A preoperative lung infection leads to adhesions and therefore increases the risk of bleeding and parenchymal injury.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a single-center study has shown decreased mean operative time of 13.1 min with thoracoscopic resection, although the difference was not statistically significant. However, the chest tube stay and length of stay were significantly longer in patients with open thoracotomy [ 20 ]. The possible explanation for these results may be the individual differences in the patients’ lesions and the different proficiency of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies added important outcomes data to the existing literature on management of congenital lung malformations. Ganarin et al 86 reported a retrospective analysis of 106 children who underwent surgical intervention for CLM between 1991 and 2020 at a single center, comparing the video‐assisted thoracoscopic (VATS) approach to thoracotomy. Procedures included sequestrectomy, atypical resection, cystectomy, and lobectomy.…”
Section: Congenital Airway and Lung Anomaliesmentioning
confidence: 99%